Counteraction to Gangsterism in Ukraine in the First Post-war Years (1945-1946) - Греченко, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
In 1945-1946 the considerable increase of criminality was marked in a republic. The complex of reasons of political, social, organizational, economic and psychological character influenced on it. An author set that factors, that entailed this criminal phenomenon, were, :  post-war devastation,  enormous scarcity of goods of daily necessity, presence of far of weapon, that was in a population (as a result of battle actions), hunger that began in 1946, full unstrength of organs of militia, insufficient professionalism of her employees, mass migration of population, is demobilization of millions of servicemen, return of far of people  from evacuation,  captivity, concentration camps, psychological consequences of war, that formed at certain part of population habit to violence. Did not assist the improvement of work of militia also an erroneous criminal law  doctrine, that dominated in jurisprudence of time of the Stalin totalitarian mode that criminality is vestige of the past, not inherent socialism and that is why her increase, - only a defect in-process militia. To the article the far of facts that testify to complication of criminogenic situation  in an investigated period and frequent displays of gangsterism in the different regions of republic is driven. The features of the normatively-legal providing of activity of organs of law and order are exposed ; character of changes is educed in organization and skilled composition of militia of Ukrainian SSR in 1945-1946. Basic directions and features of practical activity of organs of internal affairs are analysed in a fight against criminality, the results of counteraction to the militia of gangsterism are shown in an indicated period. An author marks that to the fight against criminality considerable enough attention was spared in this period, activity of militia got better gradually, but on the whole this job performances substantially influenced on reduction  of displays to gangsterism some later.